Social pacts in Europe emergence, evolution, and institutionalization - Avdagic, Sabina; Rhodes, Martin, 1956 Feb. 23-; Visser, Jelle (Oxford : Oxford University Press, 2011)
'Social Pacts in Europe' presents a full-length theoretical and comparative empirical study of new social pacts in Europe. It brings a wide range of theory to bear on social pact bargaining and institutionalization, comparing cases across Europe and providing in-depth studies of six countries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Europe -- Social policy; Europe -- Social conditions -- 21st century